Biphasic Effects of Leptin in Porcine Granulosa Cells (2003)
ABSTRACT: The direct effects of recombinant porcine leptin on porcine granulosa cells were studied to test the hypothesis that leptin, acting through the nuclear transcription factor signal transducer and activator of transcription 3 (STAT-3), modulates sterol regulatory element-binding protein 1 (SREBP1) thereby increasing steroidogenesis. In porcine granulosa cells in culture over 48 h, leptin at 10 ng/ml increased progesterone accumulation 3-fold while it was reduced by leptin at 1000 ng/ml. Leptin had no effect on progression of granulosa cells through the cell cycle nor on the frequency of cell death. Leptin treatment at 24 or 48 h of culture resulted in dose-dependent 2- to 4-fold increases in tyrosine phosphorylation of STAT-3. Leptin had a biphasic effect on the abundance of membrane-bound and transcriptionally active forms of SREBP1. In transient transfection of primary porcine granulosa cells, the plasmid expressing the transcriptionally active form of SREPB-1 induced transcription of the key regulator of steroidogenesis, the steroidogenic acute regulatory protein (StAR). StAR transcription was also increased by the low dose of leptin and was further upregulated in the presence of the SREBP plasmid. Leptin at 1000 ng/ml inhibited SREBP1-induced StAR expression. Thus, leptin, acting through STAT-3, modulates steroidogenesis in a biphasic and dose-dependent manner, and SREBP1 induction of StAR expression may be in the cascade of regulatory events.